Situation Report: Hungary, 19 March 1974 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. New Long-Distance Power Line between the USSR and Hungary Biszku on Domestic Party Policy Currency and Credit Problems in Trade with Developed Western States New Measure to Increase the Supply of Potatoes and Vegetables Cold Storage Enterprise Co-operates with Western Firms